'The challenge now is for us to remain relevant': Australian public libraries and the COVID-19 crisis. (March 2022) - Wakeling, Simon; Garner, Jane; Hider, Philip; Jamali, Hamid; Lymn, Jessie; Mansourian, Yazdan; Randell-Moon, Holly
The COVID-19 crisis has had a significant impact on public libraries around the world. In Australia, almost all public libraries experienced some period of building closure, requiring libraries to adapt their services and delivery models. This article reports findings from a large-scale survey of public library managers in Australia, which was conducted in August 2020. In particular, it presents the results of a thematic analysis of the participants' free-text responses to open questions asked as part of the survey. This analysis reveals important insights relating to responses to library closures, staffing issues, new and expanded services and programmes, relationships with parent bodies, and the role of public libraries during the crisis and beyond. While public libraries are perceived by managers to have been agile and adaptable, and to have utilised technology effectively, the findings clearly demonstrate the value to users of library buildings, with important consequences for understanding the role of public libraries.